Correlation of Dysfunctional Lens Index with Lens Opacification System III in Age Related Cataract: Doi: 10.36351/pjo.v40i2.1745 - Muzammil, Zoomar; Sharif Hashmani; Nauman Hashmani; Javeria Saleem; Aiman Monis (Pakistan Journal of Ophthalmology, 2024)
Purpose: Age-Related changes in crystalline lens opacity and lens density contribute to formation of higher order aberrations resulting in reduced quality of vision. Precise quantification of cataract is important for predicting phacodynamics and educating patient. The iTrace(a ray-tracing aberrometer) provides Dysfunctional Lens Index (DLI). This study from Pakistan investigates the relationship between LOCS III and DLI in senile cataract. Study Design: Correlational study. Place and Duration of Study: Hashmanis Hospital, Karachi from March 2021 to May 2021. Methods: This study included 44 patients with age-related cataract. Demographic characteristics and complete ophthalmic examination of eyes including Best Corrected Visual Acuity (BCVA) and slit lamp biomicroscopy were performed. Age related cataracts were graded using the Standard technique of LOCS III. I-Trace was utilized for wave front analysis to calculate DLI. Results: BCVA and LOCS III nuclear opalescence score had strongest positive linear correlation (r=0.433, P<0.01). DLI displayed a strong significant negative correlation to LOCS III Cortical Cataract (C) and LOCS III Posterior Sub-Capsular Cataract (P) score (r=-0.415 and r=-0.694; respectively). Conclusion: BCVA had insignificant and small to no correlation to LOCS III C score and P score. Whereas, DLI showed the strongest significant correlation to LOCS III C score and P score. Patient’s optical quality determined by visual symptoms are more closely associated to DLI parameter as compared to LOCS III classification. DLI can provide a better objective way to elevate age related cataract, monitor the progression and determine phacodynamics.